The role of energy demand in policymaking for a just transition to net zero: a comparative survey in the UK, the Netherlands and Germany - Nolden, C; Eyre, N; Fawcett, T; Bobrova, Y (European Council for an Energy-Efficient Economy, 2022)
Historically, energy demand reductions have been the main driver of carbon emission reductions. However, there is concern that this contribution is not recognised, and that policymaking attention remains focused on the supply side. The current and potential future role of demand in energy policymaking is explored via surveys of energy experts and stakeholders in the UK (n>77), the Netherlands (n>54) and Germany (n>80).